Olaparib Tablets as Maintenance Therapy in Patients With Platinum-Sensitive Relapsed Ovarian Cancer and a BRCA1/2 Mutation (SOLO2/ENGOT-Ov21): A Final Analysis of a Double-Blind, Randomised, Placebo-Controlled, Phase 3 Trial. Issue 9 (September 2021) - Poveda, Andrés; Floquet, Anne; Ledermann, Jonathan A.; Asher, Rebecca; Penson, Richard T.; Oza, Amit M.; Korach, Jacob; Huzarski, Tomasz; Pignata, Sandro; Friedlander, Michael; Baldoni, Alessandra; Park-Simon, Tjoung-Won; et al.
Abstract : (Abstracted from Lancet Oncol 2021;22:620–631) The poly (ADP-ribose) polymerase (PARP) inhibitor olaparib is approved as maintenance therapy in newly diagnosed ovarian cancer or in patients with platinum-sensitive, relapsed ovarian cancer regardless of BRCA1/2 mutation status. The primary analysis of the SOLO2/ENGOT-Ov21 phase 3 trial found a significant improvement in median progression-free survival associated with olaparib treatment compared with placebo in patients with platinum-sensitive, relapsed ovarian cancer and a BRCA1/2 mutation.